Islam Sasak: Sejarah Sosial Keagamaan Di Lombok (Abad XVI-XIX) - Jamaluddin Jamaluddin (JURNAL INDO-ISLAMIKA, 2011)
It is predicated that Islam, which penetrated in Lombok, was brought by Muslim merchants in the 15th century. However, according to the local sources, Islam was brought to Lombok by Sunan Prapen from Java, and not in 15th, but in 16th. Islam had been developed within the center of Islamic Kingdoms, established less than two centuries. The kingdoms had become the ruling powers. During the great periods of the Islamic kingdoms, Islam spread out massively and became the official religion of the states. Employing historical approach with three phases: heuristic, analytic or interpretative and historiography, this research discusses the penetration method of Islam in Lombok in 15th century and how it had been developing since its arrival to the 19th century.